1991
DOI: 10.1109/9.100946
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of relaxed static stability aircraft

Abstract: We formulate and solve a regulator problem for nonlinear parameter dependent dynamics. It is shown that the problem is solvable except at parameter values associated with bifurcation of the equilibrium equations and that such bifurcations are inherently linked with the system zero dynamics. These results are applied to the study of the regulation of the longitudinal dynamics of aircraft. It is shown how the ability to regulate aircraft flight path is dependent on system parameters. Computational studies focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 15 publications
1
39
0
Order By: Relevance
“…1, adapted from [2]. Notice that the surface, although smooth, may have folds, and consequently we cannot expect globally valid functions x(); u() to define equilibria.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…1, adapted from [2]. Notice that the surface, although smooth, may have folds, and consequently we cannot expect globally valid functions x(); u() to define equilibria.…”
Section: Introductionmentioning
confidence: 96%
“…If x0; u0; 0 corresponds to an equilibrium point, that is, f (x 0 ; u 0 ; 0 ) = 0 and y 0 = h(x 0 ; u 0 ; 0 ) = 0, the linear perturbation equations are _ x = @f(x0; u0; 0) @x x + @f(x0; u0; 0) @u u y = @h(x 0 ; u 0 ; 0 ) @x x + @h(x 0 ; u 0 ; 0 ) @u u: (2) Suppose, however, that we wish to construct a family of linear models in which the parameter is considered to be an independent variable. Then, in principle, we need to solve the algebraic equilibrium equations for x 0 (); u 0 () in order to obtain _ x = @f(x 0 (); u 0 (); ) @x x + @f(x 0 (); u 0 (); ) @u u = A()x + B()u y = @h(x0(); u0(); ) @x x + @h(x0(); u0(); ) @u u = C()x + D()u: The need to characterize the dependence of equilibria on the parameters is the essential and difficult aspect of the linearization problem.…”
Section: Introductionmentioning
confidence: 99%
“…The paper extends results previously introduced by the authors in. 4,5 There we showed that the ability to regulate a system was lost at points associated with bifurcation of the trim equations; ordinarily indicating stall in an aircraft. Such a bifurcation point is always associated with a degeneracy of the zero structure of the system linearization at the bifurcation point.…”
Section: Nomenclaturementioning
confidence: 99%
“…4 At the bifurcation point an arbitrarily small perturbation of parameters changes the zero structure of the system thereby requiring a fundamental change in the controller. 6 The point we wish to emphasize is that losing the capacity to regulate nonlinear flight dynamics is intimately connected to the bifurcation structure of the trim equations of the aircraft.…”
Section: It Has Redundant Regulated Variablesmentioning
confidence: 99%
See 1 more Smart Citation